A influência das tocas do tatu-canastra (Priodontes maximus) na diversidade de artrópodes - Mateus Yan de Oliveira (2023)
Ecosystem engineering is an important mechanism for maintaining and increasing species at the landscape scale. Ecosystem engineers create habitats that are used by many species. This is the case of the giant armadillo (Priodontes maximus) where their burrows serve as shelter and thermal refuge for many organisms, and 70 species of vertebrates have been documented using them. Their burrows can also favor the arthropod community since they present ideal conditions for the development of these animals. However, there is still no information about the species of arthropods that can use armadillo burrows. Therefore, the objective of this study was to evaluate the importance of giant armadillo burrows for the arthropod community and to verify whether their presence influences the abundance, richness, and diversity of species in the region. For this, we sampled 43 giant armadillo burrows and 43 control points with CO2, pitfall and moericke traps during June and September 2021 in the Pantanal of Nhecolândia, Mato Grosso do Sul, Brazil. The data generated showed that giant armadillo burrows favor more than 300 species of arthropods in the Pantanal and that their presence increases the regional species diversity by 24.3%. In addition, fleas and ticks were abundant and occurred mainly in burrows, indicating that this environment may favor the transmission of pathogens in the ecosystem. We conclude that the giant armadillo seems to be of great importance in structuring the arthropod community and that it can be an important ally in conservation, since preserving this species can indirectly favor many species of vertebrates and invertebrates that use its burrows.